Theory and Parameterization of Infections and Waves by Covid-19: A 6-Countries Data Analysis - Nieto-Chaupis, Huber (2021)
From data of USA, Japan, Germany, UK, Italy and Russian, it is claimed that the Global pandemic dictated by the dynamics of Corona virus exhibits distributions that would correspond to a morphology of Bessel-like type. Under the assumption that the pandemic contains phases of infection denoted by the velocity and acceleration of propagation of virus, then a model of polynomials given by the integer-order Bessel functions is proposed. These polynomials enter in a statistical approach to define the law of infections as function of time for the ongoing global pandemic. From this, the data evolution and their different behaviors are interpreted in terms of the different phases including the Delta variant for the recent months until August 2021.